Strategi Komunikasi Pembangunan Dalam Pengembangan Masjid Al Muhajjirin Bumi Asri - Indah Yani; Mia Rafiqa M.Lubis; M. Yudha Pratama; Herwin Herwin; M. Agustian; Irma Yusriani Simamora (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
An independent mosque is a mosque program that aims to prosper the mosque and the environment around the mosque. In managing and developing independent mosques, of course, we must pay attention to the right strategy in managing independent mosques. Independent mosque management requires proper communication as a channel for conveying information and its development. The communication needed is development communication. According to Peterson, development communication is an organized effort to use communication processes and media to improve the social and economic level that generally takes place in developing countries. This study aims to determine how development communication in the development of an independent mosque at Masjid Al-Muhajjirin Bumi Asri. This research uses qualitative research methods. Qualitative research is descriptive research and tends to use analysis. Process and meaning are highlighted in qualitative research. The theoretical basis is used as a guide so that the research focus is in accordance with the facts on the ground. The data collection method is by observing the Al-Muhajjirin Bumi Asri Mosque, interviews with mosque administrators, and devotion at the Al-Muhajjirin Bumi Asri Mosque. So the author can draw the conclusion that the development communication strategy used in the development of an independent mosque at the Al-Muhajjirin Bumi Asri Mosque is a strategy of using media, marketing, and also participatory.